Reconstructing the Meanings of Sakinah, Mawaddah, and Rahmah in the Qur'anic Verse on Marriage: A Semantic and Hermeneutical Analysis of Qur'anic Language: Rekonstruksi Makna Sakinah, Mawaddah, dan Rahmah dalam Ayat Pernikahan: Analisis Semantik dan Hermeneutika Bahasa Al-Qur'an - arif satria budi (Institut Agama Islam Sumatera Barat Pariaman, 2026)
The concepts of sakinah, mawaddah, and rahmah constitute the normative foundation of family life in the Qur'an. However, existing studies have largely examined these concepts from normative perspectives, leaving their semantic interrelationship within the Qur'anic conceptual system insufficiently explored. This study aims to reconstruct the meanings of sakinah, mawaddah, and rahmah in the Qur'anic verses on marriage by integrating Toshihiko Izutsu's semantic approach with hermeneutic interpretation. This research employs a qualitative library research design. Primary data were obtained from the Qur'an, particularly Q.S. Al-Rūm [30]: 21 and other verses containing the lexical roots s-k-n, w-d-d, and r-ḥ-m, while secondary data were drawn from Qur'anic exegeses, Arabic lexicons, Toshihiko Izutsu's works, and relevant scholarly publications. Data were analyzed by identifying the basic meaning, relational meaning, and semantic field of each concept, followed by hermeneutic interpretation. The findings reveal that sakinah represents the ultimate goal of family life, characterized by spiritual, psychological, and social tranquility; mawaddah functions as an affective force expressed through commitment and responsibility; and rahmah serves as the ethical foundation that sustains marital relationships through compassion and mutual care. These three concepts form an integrated semantic system within the Qur'anic worldview, portraying marriage as an institution founded upon tranquility, enduring love, and compassion. This study contributes to the development of Qur'anic semantic studies by integrating Izutsu's semantic theory with hermeneutic interpretation and provides a conceptual framework for strengthening premarital education, family development, and Muslim family resilience.